Socialization of Business Identification Number Towards MSME’s Sustainability In Kalianyar Village, Bondowoso Regency - Masadi, Melody Angel; Maulana, Husaini; Chandra, Alicia Cherie; Latif, Abdul; Al Munawar, Fahad Fauzan; Ikhsan, Nurman Maulana; Fahrudin, Danil Eka; Afifah, Nur; Rahmawati, Irma; Vi Safrillah, M. Rizky Eka Putra (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement), 2023)
The study recognized and identified that MSMEs in the village faced challenges due to limited knowledge about technological developments and business licensing, resulting in a lack of Business Identification Number (BIN) among business owners. This program aims to educate Micro, Small, and Medium Enterprises (MSMEs) about the importance of having a BIN and to help and assist them in obtaining this essential legal credential. Participants were guided through the steps of registering and inputting their personal data to receive a BIN. Which consisted of observation, socialization sessions, and practical assistance in obtaining BINs, also conducting a participant satisfaction rete index survey. Through this program, it is helped MSMEs overcome legal obstacles to access government programs and funding, and improve their business networks or markets. Which will result a better understanding of BINs importance, which enhanced their knowledge and professionalism in running their businesses. The participant satisfaction data from the socialization indicates an average score of 4.3, concluding that participants are satisfied with the implemented program.